Iptek Pemberdayaan Masyarakat Desa Suralaga Melalui Olahan Olerikultura Jenis Brassica Rappa Menjadi Produk Bernilai Ekonomi - her diana; Khairil Anwar (Jurnal Pengabdian Masyarakat Madani, 2021)
Mitra Promas is a group of women vegetable farmers who only work as housewives and sometimes as seasonal labourers. This PKM activity was carried out in Suralaga Village, Suralaga District, East Lombok Regency, West Nusa Tenggara from April to December with the aim of awakening the entrepreneurial spirit of housewives in this village with easy, cheap and always grown vegetable ingredients. Soil fertility in this village has the potential to grow various types of vegetables because the water system is smooth so it does not need rain water or is not seasonal. Farmers in Suralaga village tend to choose vegetables instead of rice because of the short planting time. The products that will be introduced in this PKM activity are white mustard (Brassica Rappa) which is a type of horticultural plant that has high nutritional value if used properly and with a touch of technology so that it can provide added value economically to increase people's income and create job opportunities. . The purpose of this PKM activity is to train housewives to develop an entrepreneurial spirit that has been in hiatus for a long time because basically the business group that will be fostered is a business group that has existed, namely KUB WATISA (Joint Business Group for Women Farmers and Vegetables Suralaga but it doesn't work well).